Global Encounters
XIII, 276 p.
Keywords: How has globalization impacted on development? For Harrison, the answer lies in the international political economy, and the ways in which states have managed economic globalization - from positions of strength or weakness. Key themes emerge, such as new geographies of development and the constant need for state economic action.